Creativity on Student Learning Outcomes in Al-Quran Hadith Subjects - Sawaluddin Sawaluddin; Koiy Syahbudin; Imran Rido; Supardi Ritonga (Yayasan Keluarga Guru Mandiri, 2022)
The purpose of this study was to analyze the effect of learning creativity on student learning outcomes in Al-Quran Hadith subjects at Madrasah Tsanawiyah Nurul Yaqin Pekanbaru. This research is a quantitative research by testing hypotheses or solving problems on the basis of theoretical deduction, with measurements using statistical data. This research was conducted at Madrasah Tsanawiyah (MTs) Nurul Yaqin Pekanbaru with a population of 350 people. The sampling technique used in this research is proportional stratified random sampling. The total number of sample population is known to have a set precision of 5%, then the number of samples in this study is 175 students. The data collection techniques in this study were questionnaires, tests and documentation. The data analysis technique in this study can be divided into three major stages, namely 1) Research Instrument Test Phase (Questionnaire/Questionnaire), 2) Classical Assumption Test Phase (Test Data before being analyzed by Parametric analysis), and 3) Research Hypothesis Testing Phase ( Statistical test to test the research hypothesis). Based on the results of research on the effect of learning creativity on student learning outcomes in the subjects of Al-Qur'an Hadith at MTs Nurul Yaqin Pekanbaru, which is associated with theory, it can be concluded that learning creativity (X) with student learning outcomes (Y) obtained tcount of 4.320 while ttable with a significance level of 5% and degrees of freedom (dk) = nk = 175–2 = 173 is 1.960. In this case, tcount (4,320) ttable (1,960), so that it is obtained in the area where Ho is accepted (Ha is accepted, Ho is rejected). In addition, from the table above, it can be seen that the probability value is 0.006, which means this number is smaller than the significance level (0.006 0.05), meaning that it can be concluded that the variable of learning creativity has a positive and significant influence on student learning outcomes